Awareness of cervical cancer among women attending an HIV treatment centre: a cross-sectional study from Morocco. Issue 8 (23rd August 2018) - Belglaiaa, Essaada; Souho, Tiatou; Badaoui, Latifa; Segondy, Michel; Prétet, Jean-Luc; Guenat, David; Mougin, Christiane
Abstract : Objective: To explore awareness about cervical cancer among Moroccan women attending an HIV treatment centre in Laâyoune city, Morocco. Design: A cross-sectional study was conducted from April to June 2017 using a knowledge test regarding cervical cancer, its risk factors and its prevention. Setting: HIV treatment centre at the Hospital of Moulay Hassan Ben Elmehdi in Laâyoune city, Morocco. Participants: One hundred and twenty-three HIV-positive women aged 19 years and older were recruited to this study. Results: A total of 115 women were eligible to participate in the study. The average age was 34.9±10.2 years. Few women (20%) had heard about cervical cancer and its screening, the majority (17.4%) having received information from mass media. The vast majority (79.1%) of respondents had no knowledge of cervical cancer risk factors, and 80.8% did not know any symptoms of cervical cancer. Only 13% had undergone a Pap smear test. The main reason for not seeking Pap smear was the absence of symptoms (47%). Conclusion: Our study documents poor awareness of cervical cancer. Given that the HIV-positive population is at increased risk of cervical cancer, health education programmes should be promoted to increase awareness of cervical cancer as well as access and participation in cervical cancer screening.